2014
DOI: 10.3892/br.2014.371
|View full text |Cite
|
Sign up to set email alerts
|

Association of a transcription factor 21 gene polymorphism with hypertension

Abstract: Abstract.Various loci and genes that confer susceptibility to coronary artery disease (CAD) have been identified mainly in Caucasian populations by genome-wide association studies (GWASs). As hypertension is a major risk factor for CAD, certain polymorphisms may contribute to the genetic susceptibility to CAD through affecting the predisposition to hypertension. The aim of the present study was to examine a possible association of hypertension with 29 single-nucleotide polymorphisms (SNPs) previously identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…This finding suggested that these QTLs in HCASMC may play an important role in the genetic mechanism of HCASMC mediated disease progression. All of the QTLs showed enrichment for blood pressure and hypertension phenotypes which are highly consistent with known SMC functions, and association of TCF21 with blood pressure have been identified by population studies with multiple racial ethnic groups [19][20][21]. The highly significant enrichment of breast cancer variants in the bQTL category is consistent with TCF21 being a known tumor suppressor and that is dysregulated in breast cancer, but the enrichment of breast cancer variants among the caQTLs and clQTLs is surprising and suggests a similar genomic and genetic architecture between HCASMC and breast cancer risk genes [22].…”
Section: Qtls Are Highly Associated With Gwas Cad Locisupporting
confidence: 55%
“…This finding suggested that these QTLs in HCASMC may play an important role in the genetic mechanism of HCASMC mediated disease progression. All of the QTLs showed enrichment for blood pressure and hypertension phenotypes which are highly consistent with known SMC functions, and association of TCF21 with blood pressure have been identified by population studies with multiple racial ethnic groups [19][20][21]. The highly significant enrichment of breast cancer variants in the bQTL category is consistent with TCF21 being a known tumor suppressor and that is dysregulated in breast cancer, but the enrichment of breast cancer variants among the caQTLs and clQTLs is surprising and suggests a similar genomic and genetic architecture between HCASMC and breast cancer risk genes [22].…”
Section: Qtls Are Highly Associated With Gwas Cad Locisupporting
confidence: 55%
“…Increased sortilin 1 expression leads to enhanced low-density lipoprotein (LDL)-uptake into cells, being associated with decreased plasma LDL-cholesterol, and a lower risk of coronary artery disease (21). Our previous study showed that rs599839 of PSRC1 was associated with myocardial infarction (14), hypertension (22) and dyslipidemia (hyper-LDL-cholesterolemia) (23) in Japanese individuals, with the minor G allele being protective against these conditions. The present study has shown that rs599839 of PSRC1 was associated with AF with the minor G allele representing a risk factor for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Fujimaki et al (2015) reported that rs12190287 polymorphisms are significantly associated with hypertension in Japanese populations. In the current study, we found that rs12190287 polymorphisms are associated with VSDs in a Chinese population.…”
Section: Association Of Tcf21 Rs12190287 With Vsdmentioning
confidence: 99%